The indirect health effects of malaria estimated from health advantages of the sickle cell trait - Uyoga, S; Macharia, A; Ndila, C; Nyutu, G; Shebe, M; Awuondo, K; Mturi, N; Peshu, N; Tsofa, B; Scott, J; Maitland, K; Williams, T (Nature Research, 2019)
Most estimates of the burden of malaria are based on its direct impacts; however, its true burden is likely to be greater because of its wider effects on overall health. Here we estimate the indirect impact of malaria on children's health in a case-control study, using the sickle cell trait (HbAS), a condition associated with a high degree of specific malaria resistance, as a proxy indicator for an effective intervention. We estimate the odds ratios for HbAS among cases (all children admitted to Kilifi County Hospital during 2000-2004) versus community controls. As expected, HbAS protects strongly against malaria admissions (aOR 0.26; 95%CI 0.22-0.31), but it also protects against other syndromes, including neonatal conditions (aOR 0.79; 0.67-0.93), bacteraemia (aOR 0.69; 0.54-0.88) and severe malnutrition (aOR 0.67; 0.55-0.83). The wider health impacts of malaria should be considered when estimating the potential added benefits of effective malaria interventions.